Dissecting the causal effect between gut microbiota, DHA, and urate metabolism: A large-scale bidirectional Mendelian randomization - Hou, Tianzhichao; Dai, Huajie; Wang, Qi; Hou, Yanan; Zhang, Xiaoyun; Lin, Hong; Wang, Shuangyuan; Li, Mian; Zhao, Zhiyun; Lu, Jieli; Xu, Yu; Chen, Yuhong; et al. (Frontiers in Immunology, 2023)
Abstract Objectives: To investigate the interactive causal effects between gut microbiota and host urate metabolism and explore the underlying mechanism using genetic methods. Methods: We extracted summary statistics of the abundance of 211 microbiota taxa from the MiBioGen (N =18,340), 205 microbiota metabolism pathways from the Dutch Microbiome Project (N =7738); gout from the Global Biobank Meta-analysis Initiative (N =1,448,128), urate from the CKDGen (N =288,649), and replication datasets from the Global Urate Genetics Consortium (N gout =69,374, N urate =110,347). We used linkage disequilibrium score regression and bidirectional Mendelian randomization (MR) to detect genetic causality between microbiota and gout/urate. Mediation MR and colocalization were performed to investigate potential mediators in the association between microbiota and urate metabolism. Results: Two taxa had a common causal effect on both gout and urate, where Victivallaceae family was replicable. Six taxa were commonly affected by both gout and urate, where Ruminococcusgnavusgroup genus was replicable. Genetic correlation supported significant results in MR. Two microbiota metabolic pathways were commonly affected by gout and urate. Mediation analysis indicated that Bifidobacteriales order and Bifidobacteriaceae family had protective effects on urate mediated by increasing docosahexaenoic acid. These two bacteria shared a common causal variant rs182549 with both docosahexaenoic acid and urate, which was located within MCM6/LCT locus. Conclusions: Gut microbiota and host urate metabolism had bidirectional causal association, implicating the critical role of host-microbiota crosstalk in hyperuricemic patients. Changes in gut microbiota could not only ameliorate host urate metabolism, but also become a foreboding indicator of urate metabolic diseases.